Pengaruh Kompetensi, Lingkungan Kerja Dan Dukungan Manajemen Terhadap Kinerja Karyawan PT Wika Rekayasa Konstruksi – Proyek Paket III PLTMG Biak 15 MW Kabupaten Biak Numfor - Amalia, Syarifah Ismiati; Semmaila, Baharuddin; Mapparenta, Mapparenta (Innovative: Journal Of Social Science Research, 2025)
This study aims to assess the current employee performance at PT. WIKA Rekayasa Konstruksi for the Package III PLTMG Biak 15 MW Project in Biak Numfor Regency. The variables used in this study are competence (X1), work environment (X2), management support (X3), and employee performance (Y). The sample for this study consists of 41 respondents. The research method employed is quantitative, utilizing primary data. The sampling technique used is saturated sampling. The data analysis methods used in this study include validity testing, reliability testing, normality testing, multicollinearity testing, heteroscedasticity testing, multiple linear regression analysis, simultaneous test (F test), partial test (t test), and the coefficient of determination (R2). The results of the study show that: (1) Competence has a significant positive effect on employee performance at PT. WIKA Rekayasa Konstruksi for the Package III PLTMG Biak 15 MW Project in Biak Numfor Regency. (2) Work environment has a significant positive effect on employee performance at PT. WIKA Rekayasa Konstruksi for the Package III PLTMG Biak 15 MW Project in Biak Numfor Regency. (3) Management support has a significant positive effect on employee performance at PT. WIKA Rekayasa Konstruksi for the Package III PLTMG Biak 15 MW Project in Biak Numfor Regency.